Making Science Organizations Sustainable—The Mission of the Max Planck Sustainability Network - Fardet, Tanguy; Hütten, Moritz; Lohmann, Sophie; Medawar, Evelyn; Milucka, Jana; Roesch, Jan Harald; Rolfes, Julian D.; Schweizer, Jakob (Frontiers in Sustainability, 2020)
The Max Planck Sustainability Network (MPSN) is a grassroots network within the Max Planck Society (MPG), with ~370 members from over 60 Max Planck research institutes, aiming to support sustainability within a German science association committed to fundamental research. The MPSN has adopted the twin goals of making research practices within the overall MPG more sustainable and of supporting local Sustainability Groups in making research practices at their individual institutes more sustainable. The MPSN counts members from diverse backgrounds, regarding both academic field of expertise and roles within the MPG. Its activities focus around Energy, Mobility, Supplies & Waste, Biodiversity & Food, with the ambition to assess impact and expense of each proposed measure. The network’s long-term vision is to make research more sustainable and to serve as a role model that inspires other scientific organizations to become sustainable and to optimize the operation of research and administration, which require both individual and structural changes.